ANALISIS BIAYA DAN PENDAPATAN USAHATANI BAWANG MERAH DI WILAYAH SINSINGON RAYA KECAMATAN PASSI TIMUR - Mamahit, Tita Stevina; Pangemanan, Lyndon Reinhard Jacob; Lumingkewas, Jelly Ribka Danaly (Sam Ratulangi University, 2022)
This study aims to analyze the cost structure and income of shallot farming. This research was conducted for two months in the Greater Sinsingon Region, East Passi District. Sources of data used primary data taken through direct interviews with farmers and secondary data obtained from each village secretary. The sampling method used is the Simple Random Sampling Method, which is taken at simple random with a lottery population of 65 farmers obtained a sample of 15 farmers. The analysis used in this research is descriptive analysis and then presented in tabular form. The results of the study show that the income received by farmers who cultivate shallots in the Greater Sinsingon Region is Rp 76,410,670. The largest cost incurred for farming shallots is the labor cost, which is 63.38%. The average cost incurred is Rp 1.305.955 and an average of Rp 6,400,000 thus the average income obtained by farmers is Rp 5,094,044,-.